Digital Transformation and Cyber Security: Unveiling Awareness - Undale, Padmavati Smitesh; Shinde, Vedant (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2024)
The research paper extensively examines the critical exigency for cyber security measure and advocates for increased public awareness regarding the nature of cyber-crimes, along with the proactive measures to shield against these pervasive threats. Cyber security entails a strategic practice designed to fortify system, network and program files from potential infiltrations within digital networks. Cyber-crimes predominantly focus on illicitly accessing or obliterating sensitive information, posing to substantial risk to individual and organizations alike. This comprehensive study is based on a combination of primary and secondary data sources. The primary data set encompasses responses to a meticulously crafted questionnaire provided by 298 individuals across diverse age groups, while the secondary data comprises information collated from multitude of esteemed researcher. The findings gleaned from the data analysis reveal alarming instances of individual being subjected to abuse resulting from the compromise of their social media accounts, falling victim to various forms of financial fraud and incurring substantial monetary losses through investment in spurious accounts. The study highlights the paramount needs to assess the populace’s level of awareness regarding cyber security guideline, with a considerable proportion of respondent demonstrating a commendable understanding of prescribed courses of action to undertake in the event of succumbing to cyber-crimes. The overarching objective of this study is to obtain a comprehensive understanding of cyber security.